DETERMINAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI JAKARTA ISLAMIC INDEX - Novy Adityasari; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
Dividend policy is a decision to determine the percentage of net profit of thecompany distributed to the shareholders as cash dividend which known as dividend payout ratio and the rest is percentage of retained earnings of the company. This study aims to determine factors that affect dividend policy on Manufacturing Company in Jakarta Islamic Index such as firm size, profitability, solvency and systematic risk. This study used panel data regression with Econometric Views (EViews) 8.0 as statistical analysis software. The samples are five manufacturing companies listed in Jakarta Islamic Index, during 2009 to 2015, the hypothesis test result showed that factors are firm size, profitability, solvency has significant result affecting dividend policy of manufacturing companies in Jakarta Islamic Index. REFERENCESAl-Malkawi. 2008. Husam-Aldin Nizar. Factors Influencing Corporate Dividend Decision : Evidendce from Jordanian Panel Data. International Journal of Bussiness, Vol.13, No.2, pp.177-195Brigham, Eugene F dan Joel F. Houston. 2006. Dasar – dasar Manajemen Keuangan. Buku 1, Edisi Kesepuluh. Jakarta : Salemba Empat.-----------------------. 2006. Dasar – dasar  Manajemen Keuangan. Buku 2, Edisi Kesepuluh, Jakarta : Salemba Empat.Gujarati, Damodar. 2003. Ekonometrika Dasar. Edisi Keenam. Jakarta: ErlanggaGujarati, Damodar N dan Dawn C. Porter. 2013. Dasar– dasar Ekonometrika. Buku 2. Edisi Kelima. Jakarta: Salemba Empat.Hanafi, M. Mamduh. 2004.Manajemen Keuangan. Yogyakarta: BPFE Hartono, Jogiyanto, 2010. Teori Portofollio dan Analisis Investasi, Edisi Ketujuh. Yogyakarta: BPFE YogyakartaKasmir. 2015. Analisis Laporan Keuangan. Edisi Kedelapan, Jakarta : Rajawali PersKementerian Agama Republik Indonesia. 2013. Al-Qur’an dan Terjemahannya. Solo : PT Tiga Serangkai Pustaka Mandiri. Martono dan D. Agus Harjito. 2005. Manajemen Keuangan. Yogyakarta : Ekonisia.Muhamad. 2014. Manajemen Keuangan Syari’ah (Analisis Fiqh & Keuangan). Edisi Pertama. Yogyakarta : UPP STIM YKPN.Nurmala. 2006. Pengaruh Kebijakan Dividen terhadap Harga Saham Perusahaan-perusahaan Otomotif di Bursa Efek Jakarta. Jurnal Manajemen dan Akuntansi 9 : h:17-24Otoritas Jasa Keuangan. 2015. Laporan Perkembangan Keuangan Syariah (http://www.ojk.go.id) diakses 10 Februari 2017).Riyanto, Bambang. 2001. Dasar-dasar  Pembelanjaan  Perusahaan. Edisi keempat. Yogyakarta: BPFERyandono, Muhammad Nafik H. 2009. Bursa Efek dan Investasi Syariah. Jakarta: Serambi.Sartono, Agus. 2001. Manajemen Keuangan Teori dan Aplikasi. Yogyakarta: BPFE.Sarwoko, 2005. Dasar-dasar Ekonometri. Penerbit Andi, YogyakartaShihab, Quraish. 2009. Tafsir Al-Mishbah : Pesan, Kesan dan Keserasian Al-Qur’an. Jakarta : Lentera Hati.Sudarsi, Sri. 2002. “Analisis Faktor-Faktor Yang Mempengaruhi Devident Payout Ratio pada Industri Perbankan yang Listed Di Bursa Efek Jakarta (BEJ)”. Jurnal Bisnis dan Ekonomi. Vol.9, No.1, Maret. Hal. 76-88.Sutedi, Adrian. 2011. Pasar Modal Syariah(Sarana Investasi Keuangan Berdasarkan Prinsip Syariah). Jakarta : Penerbit Sinar GrafikaSuwaldiman dan Ahmad Aziz. 2006. “Pengaruh Insider Ownership dan Risiko Pasar terhadap Kebijakan Dividen. Kajian Bisnis dan Manajemen. Vol.8 No.1, Januari 2006. Hal 53-64Tandelilin, Eduardus. 2010. Portofolio dan Investasi Teori dan Aplikasi. Edisi Pertama. Yogyakarta : Kanisius Widarjono, Agus (2007).  Ekonometrika Teori dan Aplikasi . Yogyakarta : Ekonisia  FE UIIRegulasi Peraturan Bapepam-LK Nomor II.K.1Peraturan OJK POJK No.17/POJK.04/2015Internet http://www.astra.co.id/www.idx.co.idhttp://www.indocement.co.id/ http://www.kalbe.co.id/  http://www.semenindonesia.com/https://www.unilever.co.id/www.ojk.go.id http://finance.yahoo.com www.ekbis.sindonews.com